Prevalence and antibiotic susceptibility patterns of clinical isolates of methicillin- resistant staphylococcus aureus in a tertiary care hospital in western Uganda - Stanley, Iramiot J.; Bwanga, Freddie; Itabangi, Herbert; Nakaye, Martha; Bashir, Mwambi; Bazira, Joel (British Microbiology Research Journal, 2014)
Aim: To determine the prevalence and antibiotic susceptibility patterns of clinical isolates of methicillin resistant Staphylococcus aureus isolated at Mbarara Regional Referral Hospital. Method: A total of 400 S. aureus isolates recovered from various clinical specimens at Mbarara Regional Referral Hospital were included in this study. Phenotypic screening was performed using Oxacillin. Presence of mecA gene was studied using polymerase chain reaction (PCR). The mecA positive isolates were tested for susceptibility to, Vancomycin, Imipenem, Fusidic acid, Trimethoprim/Sulfamethoxazole, Clindamycin and Linezolid using the Kirby Bauer technique. Results: Of the 300 isolates of S. aureus 31.3% (94) were phenotypically MRSA and 38% (114) had the mecA gene. All the MRSA isolates were susceptible to vancomycin and linezolid but were highly resistant to trimethoprim/sulfamethoxazole (70.2%). Of the 114MRSA isolates 19.3% (22) were multi-drug resistant S. aureus (MDR-MRSA). The study found that there was a significant difference between genotypic and phenotypic detection methods (p < 0.001). Conclusion: The prevalence of MRSA in Mbarara is high (38%) with a high resistance to trimethoprim/sulfamethoxazole. The detection of mecA gene is a good predictor of methicillin resistance in S. aureus. There is a worrying prevalence of MDR MRSA among the clinical isolates of S. aureus in South Western Uganda.
Keywords: Staphylococcus aureus; MRSA (Methicillin Resistant Staphylococcus aureus); Antibiotic; Resistant.